2021
DOI: 10.1016/j.pedn.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Former Neonatal Intensive Care Unit Fathers' Involvement 4 Years Later: A Qualitative Study

Abstract: To explore the experience of fathering a previous Newborn Intensive Care Unit (NICU) infant four years after hospitalization. Design and methods: Nineteen fathers of former NICU infants were interviewed using a semi-structured schedule. Results: Most of the fathers had children with ongoing health issues (84%). The median age of the fathers was 38 years old. Racial demographics included 12 white fathers (63%), 5 black fathers (26%), and 2 Hispanic fathers (11%). Themes that emerged included adjustments, prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Our review of the literature led us to identify several synonyms and 1 antonym for the term “bonding.” These synonyms were “closeness,”32,40 “sensitivity,” “interaction,”41,42 “feelings of bonds,”26 “love,”24 and “relationships.”35 The sole antonym was “disconnection.”5,32,38 The synonym “closeness”32,40 signifies fathers’ interactive relationship with their infant 29. Indeed, the term strongly suggests that the fathers are emotionally connected to and intimately knowledgeable of their infants 29.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our review of the literature led us to identify several synonyms and 1 antonym for the term “bonding.” These synonyms were “closeness,”32,40 “sensitivity,” “interaction,”41,42 “feelings of bonds,”26 “love,”24 and “relationships.”35 The sole antonym was “disconnection.”5,32,38 The synonym “closeness”32,40 signifies fathers’ interactive relationship with their infant 29. Indeed, the term strongly suggests that the fathers are emotionally connected to and intimately knowledgeable of their infants 29.…”
Section: Resultsmentioning
confidence: 99%
“…In past research, fathers reported that their initial investment in building a relationship with their prematurely born infants in NICUs helped strengthen the father–child bonding relationship years later 40. Nevertheless, recent evidence indicates that suboptimal bonding in NICUs continues to be an issue after neonatal discharge 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, mothers are overrepresented (43 versus 13), for example, and there is a difference in the way mothers cope with a preterm birth compared with fathers (Shaw et al, 2006). Actually, there is still a lack of research into the experiences and need for mental support of fathers (Clarkson & Hearn, 2021; Kaplan & Knoll, 2018). It is important to pay attention to fathers in future research on this issue.…”
Section: Discussionmentioning
confidence: 99%